2013
DOI: 10.1111/jvim.12158
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Antemortem Diagnosis of Equine Protozoal Myeloencephalitis (EPM) Based on Detecting Intrathecal Antibodies againstSarcocystis neuronaUsing the SnSAG2 and SnSAG4/3ELISAs

Abstract: Background: Recent work demonstrated the value of antigen-specific antibody indices (AI and C-value) to detect intrathecal antibody production against Sarcocystis neurona for antemortem diagnosis of equine protozoal myeloencephalitis (EPM).Objectives: The study was conducted to assess whether the antigen-specific antibody indices can be reduced to a simple serum : cerebrospinal fluid (CSF) titer ratio to achieve accurate EPM diagnosis.Animals: Paired serum and CSF samples from 128 horses diagnosed by postmorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…Additionally, there is widespread exposure of horses to the primary causative agent Sarcocystis neurona ; seroprevalence in the United States ranges from 33% to 89% depending on the region 1. However, annual incidence of clinical disease is still <1%2 and is thought to occur when parasites invade and propagate in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is widespread exposure of horses to the primary causative agent Sarcocystis neurona ; seroprevalence in the United States ranges from 33% to 89% depending on the region 1. However, annual incidence of clinical disease is still <1%2 and is thought to occur when parasites invade and propagate in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that minor blood contamination of the CSF sample (ie, up to 10,000 red cells per μL) will not confound the assay results. Subsequently, 2 additional studies examining a more extensive collection of horses with neurologic disease showed that a simple serum:CSF antibody titer ratio was sufficient in many cases for an accurate diagnosis of EPM caused by S. neurona 71, 72. Although use of a serum:CSF titer ratio should be equally effective for diagnosis of EPM caused by N. hughesi , an optimal serum:CSF titer ratio cut‐off needs to be established.…”
Section: Immunodiagnostic Testingmentioning
confidence: 99%
“…Descriptions of testing options and reported test performance are shown in Table 1 71, 72, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93. All tests can be performed on serum or CSF, and none is considered a gold standard.…”
Section: Immunodiagnostic Testingmentioning
confidence: 99%
See 2 more Smart Citations